A transference approach to a Roth-type theorem in the squares - Browning, Timothy D; Prendiville, Sean (International Mathematics Research Notices)
We show that any subset of the squares of positive relative upper density contains nontrivial solutions to a translation-invariant linear equation in five or more variables, with explicit quantitative bounds. As a consequence, we establish the partition regularity of any diagonal quadric in five or more variables whose coefficients sum to zero. Unlike previous approaches, which are limited to equations in seven or more variables, we employ transference technology of Green to import bounds from the linear setting.

Norm forms for arbitrary number fields as products of linear polynomials - Browning, Timothy D; Matthiesen, Lilian (Annales Scientifiques de l'Ecole Normale Superieure)
Given a number field K/Q and a polynomial P ε Q [t], all of whose roots are Q, let X be the variety defined by the equation NK (x) = P (t). Combining additive combinatiorics with descent we show that the Brauer-Manin obstruction is the only obstruction to the Hesse principle and weak approximation on any smooth and projective model of X.

Improvements in Birch's theorem on forms in many variables - Browning, Timothy D; Prendiville, Sean (Journal fur die Reine und Angewandte Mathematik)
We show that a non-singular integral form of degree d is soluble over the integers if and only if it is soluble over ℝ and over ℚp for all primes p, provided that the form has at least (d - 1/2 √d)2d variables. This improves on a longstanding result of Birch.

Many cubic surfaces contain rational points - Browning, Timothy D (Mathematika)
Building on recent work of Bhargava, Elkies and Schnidman and of Kriz and Li, we produce infinitely many smooth cubic surfaces defined over the field of rational numbers that contain rational points.

Varieties with too many rational points - Browning, Timothy D; Loughran, Daniel (Mathematische Zeitschrift)
We investigate Fano varieties defined over a number field that contain subvarieties whose number of rational points of bounded height is comparable to the total number on the variety.

Bottom up engineering of thermoelectric nanomaterials and devices from solution processed nanoparticle building blocks - Ortega, Silvia; Ibanez Sabate, Maria; Liu, Yu; Zhang, Yu; Kovalenko, Maksym; Cadavid, Doris; Cabot, Andreu (Chemical Society Reviews)
The conversion of thermal energy to electricity and vice versa by means of solid state thermoelectric devices is extremely appealing. However, its cost-effectiveness is seriously hampered by the relatively high production cost and low efficiency of current thermoelectric materials and devices. To overcome present challenges and enable a successful deployment of thermoelectric systems in their wide application range, materials with significantly improved performance need to be developed. Nanostructuration can help in several ways to reach the very particular group of properties required to achieve high thermoelectric performances. Nanodomains inserted within a crystalline matrix can provide large charge carrier concentrations without strongly influencing their mobility, thus allowing to reach very high electrical conductivities. Nanostructured materials contain numerous grain boundaries that efficiently scatter mid- and long-wavelength phonons thus reducing the thermal conductivity. Furthermore, nanocrystalline domains can enhance the Seebeck coefficient by modifying the density of states and/or providing type- and energy-dependent charge carrier scattering. All these advantages can only be reached when engineering a complex type of material, nanocomposites, with exquisite control over structural and chemical parameters at multiple length scales. Since current conventional nanomaterial production technologies lack such level of control, alternative strategies need to be developed and adjusted to the specifics of the field. A particularly suitable approach to produce nanocomposites with unique level of control over their structural and compositional parameters is their bottom-up engineering from solution-processed nanoparticles. In this work, we review the state-of-the-art of this technology applied to the thermoelectric field, including the synthesis of nanoparticles of suitable materials with precisely engineered composition and surface chemistry, their combination and consolidation into nanostructured materials, the strategies to electronically dope such materials and the attempts to fabricate thermoelectric devices using nanoparticle-based nanopowders and inks.

Formation of a repressive complex in the mammalian circadian clock is mediated by the secondary pocket of CRY1 - Michael, Alicia Kathleen; Fribourgh, Jennifer L.; Chelliah, Yogarany; Sandate, Colby R.; Hura, Greg L.; Schneidman-Duhovny, Dina; Tripathi, Sarvind M.; Takahashi, Joseph S.; Partch, Carrie L. (Proceedings of the National Academy of Sciences)
The basic helix–loop–helix PAS domain (bHLH-PAS) transcription factor CLOCK:BMAL1 (brain and muscle Arnt-like protein 1) sits at the core of the mammalian circadian transcription/translation feedback loop. Precise control of CLOCK:BMAL1 activity by coactivators and repressors establishes the ∼24-h periodicity of gene expression. Formation of a repressive complex, defined by the core clock proteins cryptochrome 1 (CRY1):CLOCK:BMAL1, plays an important role controlling the switch from repression to activation each day. Here we show that CRY1 binds directly to the PAS domain core of CLOCK:BMAL1, driven primarily by interaction with the CLOCK PAS-B domain. Integrative modeling and solution X-ray scattering studies unambiguously position a key loop of the CLOCK PAS-B domain in the secondary pocket of CRY1, analogous to the antenna chromophore-binding pocket of photolyase. CRY1 docks onto the transcription factor alongside the PAS domains, extending above the DNA-binding bHLH domain. Single point mutations at the interface on either CRY1 or CLOCK disrupt formation of the ternary complex, highlighting the importance of this interface for direct regulation of CLOCK:BMAL1 activity by CRY1.
Keywords: Multidisciplinary

Animal cryptochromes: Divergent roles in light perception, circadian timekeeping and beyond - Michael, Alicia Kathleen; Fribourgh, Jennifer L.; Van Gelder, Russell N.; Partch, Carrie L. (Photochemistry and Photobiology)
Cryptochromes are evolutionarily related to the light‐dependent DNA repair enzyme photolyase, serving as major regulators of circadian rhythms in insects and vertebrate animals. There are two types of cryptochromes in the animal kingdom: Drosophila ‐like CRYs that act as nonvisual photopigments linking circadian rhythms to the environmental light/dark cycle, and vertebrate‐like CRYs that do not appear to sense light directly, but control the generation of circadian rhythms by acting as transcriptional repressors. Some animals have both types of CRYs, while others possess only one. Cryptochromes have two domains, the photolyase homology region (PHR) and an extended, intrinsically disordered C‐terminus. While all animal CRYs share a high degree of sequence and structural homology in their PHR domains, the C‐termini are divergent in both length and sequence identity. Recently, cryptochrome function has been shown to extend beyond its pivotal role in circadian clocks, participating in regulation of the DNA damage response, cancer progression and glucocorticoid signaling, as well as being implicated as possible magnetoreceptors. In this review, we provide a historical perspective on the discovery of animal cryptochromes, examine similarities and differences of the two types of animal cryptochromes and explore some of the divergent roles for this class of proteins.
Keywords: Physical and Theoretical Chemistry; General Medicine; Biochemistry

Structural dynamics of RbmA governs plasticity of Vibrio cholerae biofilms - Fong, Jiunn CN; Rogers, Andrew; Michael, Alicia Kathleen; Parsley, Nicole C; Cornell, William-Cole; Lin, Yu-Cheng; Singh, Praveen K; Hartmann, Raimo; Drescher, Knut; Vinogradov, Evgeny; Dietrich, Lars EP; Partch, Carrie L; et al. (eLife)
Biofilm formation is critical for the infection cycle of Vibrio cholerae. Vibrio exopolysaccharides (VPS) and the matrix proteins RbmA, Bap1 and RbmC are required for the development of biofilm architecture. We demonstrate that RbmA binds VPS directly and uses a binary structural switch within its first fibronectin type III (FnIII-1) domain to control RbmA structural dynamics and the formation of VPS-dependent higher-order structures. The structural switch in FnIII-1 regulates interactions in trans with the FnIII-2 domain, leading to open (monomeric) or closed (dimeric) interfaces. The ability of RbmA to switch between open and closed states is important for V. cholerae biofilm formation, as RbmA variants with switches that are locked in either of the two states lead to biofilms with altered architecture and structural integrity.
Keywords: General Immunology and Microbiology; General Biochemistry; Genetics and Molecular Biology; General Medicine; General Neuroscience

A slow conformational switch in the BMAL1 transactivation domain modulates circadian rhythms - Gustafson, Chelsea L.; Parsley, Nicole C.; Asimgil, Hande; Lee, Hsiau-Wei; Ahlbach, Christopher; Michael, Alicia Kathleen; Xu, Haiyan; Williams, Owen L.; Davis, Tara L.; Liu, Andrew C.; Partch, Carrie L. (Molecular Cell)
The C-terminal transactivation domain (TAD) of BMAL1 (brain and muscle ARNT-like 1) is a regulatory hub for transcriptional coactivators and repressors that compete for binding and, consequently, contributes to period determination of the mammalian circadian clock. Here, we report the discovery of two distinct conformational states that slowly exchange within the dynamic TAD to control timing. This binary switch results from cis/trans isomerization about a highly conserved Trp-Pro imide bond in a region of the TAD that is required for normal circadian timekeeping. Both cis and trans isomers interact with transcriptional regulators, suggesting that isomerization could serve a role in assembling regulatory complexes in vivo. Toward this end, we show that locking the switch into the trans isomer leads to shortened circadian periods. Furthermore, isomerization is regulated by the cyclophilin family of peptidyl-prolyl isomerases, highlighting the potential for regulation of BMAL1 protein dynamics in period determination.
Keywords: Cell Biology; Molecular Biology

Structural basis of the day-night transition in a bacterial circadian clock - Tseng, Roger; Goularte, Nicolette F.; Chavan, Archana; Luu, Jansen; Cohen, Susan E.; Chang, Yong-Gang; Heisler, Joel; Li, Sheng; Michael, Alicia Kathleen; Tripathi, Sarvind; Golden, Susan S.; LiWang, Andy; et al. (Science)
Circadian clocks are ubiquitous timing systems that induce rhythms of biological activities in synchrony with night and day. In cyanobacteria, timing is generated by a posttranslational clock consisting of KaiA, KaiB, and KaiC proteins and a set of output signaling proteins, SasA and CikA, which transduce this rhythm to control gene expression. Here, we describe crystal and nuclear magnetic resonance structures of KaiB-KaiC,KaiA-KaiB-KaiC, and CikA-KaiB complexes. They reveal how the metamorphic properties of KaiB, a protein that adopts two distinct folds, and the post–adenosine triphosphate hydrolysis state of KaiC create a hub around which nighttime signaling events revolve, including inactivation of KaiA and reciprocal regulation of the mutually antagonistic signaling proteins, SasA and CikA.
Keywords: Multidisciplinary

Deep HST imaging in 47 Tucanae: A global dynamical model - Heyl, J.; Caiazzo, Ilaria; Richer, H.; Anderson, J.; Kalirai, J.; Parada, J. (The Astrophysical Journal)
Multi-epoch observations with the Advanced Camera Survey and WFC3 on the Hubble Space Telescope provide a unique and comprehensive probe of stellar dynamics within 47 Tucanae. We confront analytic models of the globular cluster with the observed stellar proper motions that probe along the main sequence from just above 0.8–0.1M⊙ as well as white dwarfs younger than 1 Gyr. One field lies just beyond the half-light radius where dynamical models (e.g., lowered Maxwellian distributions) make robust predictions for the stellar proper motions. The observed proper motions in this outer field show evidence for anisotropy in the velocity distribution as well as skewness; the latter is evidence of rotation. The measured velocity dispersions and surface brightness distributions agree in detail with a rotating anisotropic model of the stellar distribution function with mild dependence of the proper-motion dispersion on mass. However, the best-fitting models underpredict the rotation and skewness of the stellar velocities. In the second field, centered on the core of the cluster, the mass segregation in proper motion is much stronger. Nevertheless the model developed in the outer field can be extended inward by taking this mass segregation into account in a heuristic fashion. The proper motions of the main-sequence stars yield a mass estimate of the cluster of at a distance of 4.7 kpc. By comparing the proper motions of a sample of giant and subgiant stars with the observed radial velocities we estimate the distance to the cluster kinematically to be 4.29 ± 0.47 kpc.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

The onset of convective coupling and freezing in the white dwarfs of 47 Tucanae - Obertas, Alysa; Caiazzo, Ilaria; Heyl, Jeremy; Richer, Harvey; Kalirai, Jason; Tremblay, Pier-Emmanuel (Monthly Notices of the Royal Astronomical Society)
Using images from the Hubble Space Telescope Advanced Camera for Surveys, we measure the rate of cooling of white dwarfs in the globular cluster 47 Tucanae and compare it to modelled cooling curves. We examine the effects of the outer convective envelope reaching the nearly isothermal degenerate core and the release of latent heat during core crystallization on the white dwarf cooling rates. For white dwarfs typical of 47 Tuc, the onset of these effects occur at similar times. The latent heat released during crystallization is a small heat source. In contrast, the heat reservoir of the degenerate core is substantially larger. When the convective envelope reaches the nearly isothermal interior of the white dwarf, the star becomes brighter than it would be in the absence of this effect. Our modelled cooling curves that include this convective coupling closely match the observed luminosity function of the white dwarfs in 47 Tuc.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

Magnetar giant flare high-energy emission - Elenbaas, C.; Huppenkothen, D.; Omand, C.; Watts, A. L.; Bissaldi, E.; Caiazzo, Ilaria; Heyl, J. (Monthly Notices of the Royal Astronomical Society)
High-energy (>250 keV) emission has been detected persisting for several tens of seconds after the initial spike of magnetar giant flares (GFs). It has been conjectured that this emission might arise via inverse Compton scattering in a highly extended corona generated by super-Eddington outflows high up in the magnetosphere. In this paper, we undertake a detailed examination of this model. We investigate the properties of the required scatterers, and whether the mechanism is consistent with the degree of pulsed emission observed in the tail of the GF. We conclude that the mechanism is consistent with current data, although the origin of the scattering population remains an open question. We propose an alternative picture in which the emission is closer to that star and is dominated by synchrotron radiation. The Reuven Ramaty High Energy Solar Spectroscopic Imager observations of the 2004 December flare modestly favour this latter picture. We assess the prospects for the Fermi Gamma-ray Space Telescope to detect and characterize a similar high-energy component in a future GF. Such a detection should help to resolve some of the outstanding issues.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

Polluting white dwarfs with perturbed exo-comets - Caiazzo, Ilaria; Heyl, Jeremy S. (Monthly Notices of the Royal Astronomical Society)
We present a model to account for the observed debris discs around young white dwarfs and the presence of metal lines in their spectra. Stellar evolution models predict that the mass-loss on the AGB will be pulsed; furthermore, observations indicate that the bulk of the mass-loss occurs on the AGB. In this case, if the progenitors of the white dwarfs had remnants of planetary formation like the Sun’s Oort cloud or the Kuiper Belt and a planet lying within that cloud or nearby, we find that up to 2 per cent of the planetesimals will fall either into planet-crossing orbits or into chaotic regions after the mass-loss, depending on the location and mass of the planet (from Mars to Neptune). This yields a sufficient mass of comets that can be scattered towards the star, form a debris disc and pollute the atmosphere.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

Sequence-specific thermodynamic properties of nucleic acids influence both transcriptional pausing and backtracking in yeast - Lukacisin, Martin; Landon, Matthieu; Jajoo, Rishi (PLoS One)
RNA Polymerase II pauses and backtracks during transcription, with many consequences for gene expression and cellular physiology. Here, we show that the energy required to melt double-stranded nucleic acids in the transcription bubble predicts pausing in Saccharomyces cerevisiae far more accurately than nucleosome roadblocks do. In addition, the same energy difference also determines when the RNA polymerase backtracks instead of continuing to move forward. This data-driven model corroborates—in a genome wide and quantitative manner—previous evidence that sequence-dependent thermodynamic features of nucleic acids influence both transcriptional pausing and backtracking.

The dynamic cytokine niche - Assen, Frank P; Sixt, Michael K (Immunity)
Immune cells communicate using cytokine signals, but the quantitative rules of this communication aren't clear. In this issue of Immunity, Oyler-Yaniv et al. (2017) suggest that the distribution of a cytokine within a lymphatic organ is primarily governed by the local density of cells consuming it.

PirB regulates asymmetries in hippocampal circuitry - Ukai, Hikari; Kawahara, Aiko; Hirayama, Keiko; Case, Matthew J; Aino, Shotaro; Miyabe, Masahiro; Wakita, Ken; Oogi, Ryohei; Kasayuki, Michiyo; Kawashima, Shihomi; Sugimoto, Shunichi; Chikamatsu, Kanako; et al. (PLoS One)
Left-right asymmetry is a fundamental feature of higher-order brain structure; however, the molecular basis of brain asymmetry remains unclear. We recently identified structural and functional asymmetries in mouse hippocampal circuitry that result from the asymmetrical distribution of two distinct populations of pyramidal cell synapses that differ in the density of the NMDA receptor subunit GluRε2 (also known as NR2B, GRIN2B or GluN2B). By examining the synaptic distribution of ε2 subunits, we previously found that β2-microglobulin-deficient mice, which lack cell surface expression of the vast majority of major histocompatibility complex class I (MHCI) proteins, do not exhibit circuit asymmetry. In the present study, we conducted electrophysiological and anatomical analyses on the hippocampal circuitry of mice with a knockout of the paired immunoglobulin-like receptor B (PirB), an MHCI receptor. As in β2-microglobulin-deficient mice, the PirB-deficient hippocampus lacked circuit asymmetries. This finding that MHCI loss-of-function mice and PirB knockout mice have identical phenotypes suggests that MHCI signals that produce hippocampal asymmetries are transduced through PirB. Our results provide evidence for a critical role of the MHCI/PirB signaling system in the generation of asymmetries in hippocampal circuitry.

Green-light-induced inactivation of receptor signaling using cobalamin-binding domains - Kainrath, Stephanie; Stadler, Manuela; Gschaider-Reichhart, Eva; Distel, Martin; Janovjak, Harald L (Angewandte Chemie - International Edition)
Optogenetics and photopharmacology provide spatiotemporally precise control over protein interactions and protein function in cells and animals. Optogenetic methods that are sensitive to green light and can be used to break protein complexes are not broadly available but would enable multichromatic experiments with previously inaccessible biological targets. Herein, we repurposed cobalamin (vitamin B12) binding domains of bacterial CarH transcription factors for green-light-induced receptor dissociation. In cultured cells, we observed oligomerization-induced cell signaling for the fibroblast growth factor receptor 1 fused to cobalamin-binding domains in the dark that was rapidly eliminated upon illumination. In zebrafish embryos expressing fusion receptors, green light endowed control over aberrant fibroblast growth factor signaling during development. Green-light-induced domain dissociation and light-inactivated receptors will critically expand the optogenetic toolbox for control of biological processes.

Methodological advances in auxin and cytokinin biology - Hurny, Andrej; Benková, Eva (Auxins and Cytokinins in Plant Biology)
The history of auxin and cytokinin biology including the initial discoveries by father–son duo Charles Darwin and Francis Darwin (1880), and Gottlieb Haberlandt (1919) is a beautiful demonstration of unceasing continuity of research. Novel findings are integrated into existing hypotheses and models and deepen our understanding of biological principles. At the same time new questions are triggered and hand to hand with this new methodologies are developed to address these new challenges.

The RNA-binding protein tristetraprolin schedules apoptosis of pathogen-engaged neutrophils during bacterial infection - Ebner, Florian; Sedlyarov, Vitaly; Tasciyan, Saren; Ivin, Masa; Kratochvill, Franz; Gratz, Nina; Kenner, Lukas; Villunger, Andreas; Sixt, Michael K; Kovarik, Pavel (The Journal of Clinical Investigation)
Protective responses against pathogens require a rapid mobilization of resting neutrophils and the timely removal of activated ones. Neutrophils are exceptionally short-lived leukocytes, yet it remains unclear whether the lifespan of pathogen-engaged neutrophils is regulated differently from that in the circulating steady-state pool. Here, we have found that under homeostatic conditions, the mRNA-destabilizing protein tristetraprolin (TTP) regulates apoptosis and the numbers of activated infiltrating murine neutrophils but not neutrophil cellularity. Activated TTP-deficient neutrophils exhibited decreased apoptosis and enhanced accumulation at the infection site. In the context of myeloid-specific deletion of Ttp, the potentiation of neutrophil deployment protected mice against lethal soft tissue infection with Streptococcus pyogenes and prevented bacterial dissemination. Neutrophil transcriptome analysis revealed that decreased apoptosis of TTP-deficient neutrophils was specifically associated with elevated expression of myeloid cell leukemia 1 (Mcl1) but not other antiapoptotic B cell leukemia/ lymphoma 2 (Bcl2) family members. Higher Mcl1 expression resulted from stabilization of Mcl1 mRNA in the absence of TTP. The low apoptosis rate of infiltrating TTP-deficient neutrophils was comparable to that of transgenic Mcl1-overexpressing neutrophils. Our study demonstrates that posttranscriptional gene regulation by TTP schedules the termination of the antimicrobial engagement of neutrophils. The balancing role of TTP comes at the cost of an increased risk of bacterial infections.

Interstitial fluid osmolarity modulates the action of differential tissue surface tension in progenitor cell segregation during gastrulation - Krens, Gabriel; Veldhuis, Jim; Barone, Vanessa; Capek, Daniel; Maître, Jean-Léon; Brodland, Wayne; Heisenberg, Carl-Philipp J (Development)
The segregation of different cell types into distinct tissues is a fundamental process in metazoan development. Differences in cell adhesion and cortex tension are commonly thought to drive cell sorting by regulating tissue surface tension (TST). However, the role that differential TST plays in cell segregation within the developing embryo is as yet unclear. Here, we have analyzed the role of differential TST for germ layer progenitor cell segregation during zebrafish gastrulation. Contrary to previous observations that differential TST drives germ layer progenitor cell segregation in vitro, we show that germ layers display indistinguishable TST within the gastrulating embryo, arguing against differential TST driving germ layer progenitor cell segregation in vivo. We further show that the osmolarity of the interstitial fluid (IF) is an important factor that influences germ layer TST in vivo, and that lower osmolarity of the IF compared with standard cell culture medium can explain why germ layers display differential TST in culture but not in vivo. Finally, we show that directed migration of mesendoderm progenitors is required for germ layer progenitor cell segregation and germ layer formation.

Complex chromosomal neighborhood effects determine the adaptive potential of a gene under selection - Steinrück, Magdalena; Guet, Calin C (eLife)
How the organization of genes on a chromosome shapes adaptation is essential for understanding evolutionary paths. Here, we investigate how adaptation to rapidly increasing levels of antibiotic depends on the chromosomal neighborhood of a drug-resistance gene inserted at different positions of the Escherichia coli chromosome. Using a dual-fluorescence reporter that allows us to distinguish gene amplifications from other up-mutations, we track in real-time adaptive changes in expression of the drug-resistance gene. We find that the relative contribution of several mutation types differs systematically between loci due to properties of neighboring genes: essentiality, expression, orientation, termination, and presence of duplicates. These properties determine rate and fitness effects of gene amplification, deletions, and mutations compromising transcriptional termination. Thus, the adaptive potential of a gene under selection is a system-property with a complex genetic basis that is specific for each chromosomal locus, and it can be inferred from detailed functional and genomic data.

Stress induced mutagenesis: Stress diversity facilitates the persistence of mutator genes - Lukacisinova, Marta; Novak, Sebastian; Paixao, Tiago (PLoS Computational Biology)
Mutator strains are expected to evolve when the availability and effect of beneficial mutations are high enough to counteract the disadvantage from deleterious mutations that will inevitably accumulate. As the population becomes more adapted to its environment, both availability and effect of beneficial mutations necessarily decrease and mutation rates are predicted to decrease. It has been shown that certain molecular mechanisms can lead to increased mutation rates when the organism finds itself in a stressful environment. While this may be a correlated response to other functions, it could also be an adaptive mechanism, raising mutation rates only when it is most advantageous. Here, we use a mathematical model to investigate the plausibility of the adaptive hypothesis. We show that such a mechanism can be mantained if the population is subjected to diverse stresses. By simulating various antibiotic treatment schemes, we find that combination treatments can reduce the effectiveness of second-order selection on stress-induced mutagenesis. We discuss the implications of our results to strategies of antibiotic therapy.

Toward a quantitative understanding of antibiotic resistance evolution - Lukacisinova, Marta; Bollenbach, Mark Tobias (Current Opinion in Biotechnology)
The rising prevalence of antibiotic resistant bacteria is an increasingly serious public health challenge. To address this problem, recent work ranging from clinical studies to theoretical modeling has provided valuable insights into the mechanisms of resistance, its emergence and spread, and ways to counteract it. A deeper understanding of the underlying dynamics of resistance evolution will require a combination of experimental and theoretical expertise from different disciplines and new technology for studying evolution in the laboratory. Here, we review recent advances in the quantitative understanding of the mechanisms and evolution of antibiotic resistance. We focus on key theoretical concepts and new technology that enables well-controlled experiments. We further highlight key challenges that can be met in the near future to ultimately develop effective strategies for combating resistance.

Non-polynomial worst case analysis of recursive programs - Chatterjee, Krishnendu; Fu, Hongfei; Goharshady, Amir
We study the problem of developing efficient approaches for proving worst-case bounds of non-deterministic recursive programs. Ranking functions are sound and complete for proving termination and worst-case bounds of non-recursive programs. First, we apply ranking functions to recursion, resulting in measure functions, and show that they provide a sound and complete approach to prove worst-case bounds of non-deterministic recursive programs. Our second contribution is the synthesis of measure functions in non-polynomial forms. We show that non-polynomial measure functions with logarithm and exponentiation can be synthesized through abstraction of logarithmic or exponentiation terms, Farkas’ Lemma, and Handelman’s Theorem using linear programming. While previous methods obtain worst-case polynomial bounds, our approach can synthesize bounds of the form O(n log n) as well as O(nr) where r is not an integer. We present experimental results to demonstrate that our approach can efficiently obtain worst-case bounds of classical recursive algorithms such as Merge-Sort, Closest-Pair, Karatsuba’s algorithm and Strassen’s algorithm.

JTDec: A tool for tree decompositions in soot - Chatterjee, Krishnendu; Goharshady, Amir; Pavlogiannis, Andreas
The notion of treewidth of graphs has been exploited for faster algorithms for several problems arising in verification and program analysis. Moreover, various notions of balanced tree decompositions have been used for improved algorithms supporting dynamic updates and analysis of concurrent programs. In this work, we present a tool for constructing tree-decompositions of CFGs obtained from Java methods, which is implemented as an extension to the widely used Soot framework. The experimental results show that our implementation on real-world Java benchmarks is very efficient. Our tool also provides the first implementation for balancing tree-decompositions. In summary, we present the first tool support for exploiting treewidth in the static analysis problems on Java programs.

Friction forces position the neural anlage - Smutny, Michael; Ákos, Zsuzsa; Grigolon, Silvia; Shamipour, Shayan; Ruprecht, Verena; Capek, Daniel; Behrndt, Martin; Papusheva, Ekaterina; Tada, Masazumi; Hof, Björn; Vicsek, Tamás; Salbreux, Guillaume; et al. (Nature Cell Biology)
During embryonic development, mechanical forces are essential for cellular rearrangements driving tissue morphogenesis. Here, we show that in the early zebrafish embryo, friction forces are generated at the interface between anterior axial mesoderm (prechordal plate, ppl) progenitors migrating towards the animal pole and neurectoderm progenitors moving in the opposite direction towards the vegetal pole of the embryo. These friction forces lead to global rearrangement of cells within the neurectoderm and determine the position of the neural anlage. Using a combination of experiments and simulations, we show that this process depends on hydrodynamic coupling between neurectoderm and ppl as a result of E-cadherin-mediated adhesion between those tissues. Our data thus establish the emergence of friction forces at the interface between moving tissues as a critical force-generating process shaping the embryo.

An effective feedback loop between cell-cell contact duration and morphogen signaling determines cell fate - Barone, Vanessa; Lang, Moritz; Krens, Gabriel; Pradhan, Saurabh; Shamipour, Shayan; Sako, Keisuke; Sikora, Mateusz K; Guet, Calin C; Heisenberg, Carl-Philipp J (Developmental Cell)
Cell-cell contact formation constitutes an essential step in evolution, leading to the differentiation of specialized cell types. However, remarkably little is known about whether and how the interplay between contact formation and fate specification affects development. Here, we identify a positive feedback loop between cell-cell contact duration, morphogen signaling, and mesendoderm cell-fate specification during zebrafish gastrulation. We show that long-lasting cell-cell contacts enhance the competence of prechordal plate (ppl) progenitor cells to respond to Nodal signaling, required for ppl cell-fate specification. We further show that Nodal signaling promotes ppl cell-cell contact duration, generating a positive feedback loop between ppl cell-cell contact duration and cell-fate specification. Finally, by combining mathematical modeling and experimentation, we show that this feedback determines whether anterior axial mesendoderm cells become ppl or, instead, turn into endoderm. Thus, the interdependent activities of cell-cell signaling and contact formation control fate diversification within the developing embryo.

Cell polarity in cerebral cortex development - cellular architecture shaped by biochemical networks - Hansen, Andi H; Düllberg, Christian F; Mieck, Christine; Loose, Martin; Hippenmeyer, Simon (Frontiers in Cellular Neuroscience)
The human cerebral cortex is the seat of our cognitive abilities and composed of an extraordinary number of neurons, organized in six distinct layers. The establishment of specific morphological and physiological features in individual neurons needs to be regulated with high precision. Impairments in the sequential developmental programs instructing corticogenesis lead to alterations in the cortical cytoarchitecture which is thought to represent the major underlying cause for several neurological disorders including neurodevelopmental and psychiatric diseases. In this review we discuss the role of cell polarity at sequential stages during cortex development. We first provide an overview of morphological cell polarity features in cortical neural stem cells and newly-born postmitotic neurons. We then synthesize a conceptual molecular and biochemical framework how cell polarity is established at the cellular level through a break in symmetry in nascent cortical projection neurons. Lastly we provide a perspective how the molecular mechanisms applying to single cells could be probed and integrated in an in vivo and tissue-wide context.